1995
DOI: 10.3168/jds.s0022-0302(95)76842-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Growth Hormone-Releasing Factor and Somatotropin: Thyroid Status of Lactating, Primiparous Cows

Abstract: Effects of recombinant bovine growth hormone-releasing factor and recombinant bST on thyroxine 5'-deiodinase activities of liver and mammary gland were studied for lactating cows. Beginning on d 118 of lactation, 30 primiparous Holsteins received continuous infusions of 12 mg/d of releasing factor or 29 mg/d of bST or served as uninfused controls for 63 d. Blood samples were collected on d 1, 29, and 57, and samples of whole milk were collected at the early afternoon milking on d -5, 30, and 58. Liver and mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
1
24
2
Order By: Relevance
“…The fact that only T3, and not T4, significantly increased could be a consequence of a different liver monodeiodination activity; nevertheless, our result is the opposite of that obtained by Kahl et al (1995). It can be suggested that the rise of T3 concentration could be linked to the marked rise in glucose concentration observed in late lactation only (Bertoni et al, 1983).…”
Section: Discussioncontrasting
confidence: 56%
“…The fact that only T3, and not T4, significantly increased could be a consequence of a different liver monodeiodination activity; nevertheless, our result is the opposite of that obtained by Kahl et al (1995). It can be suggested that the rise of T3 concentration could be linked to the marked rise in glucose concentration observed in late lactation only (Bertoni et al, 1983).…”
Section: Discussioncontrasting
confidence: 56%
“…us, thyroid hormone status may influence feed intake, which subsequently affects IGF-I levels, and may modify IGF-I concentrations through effects on GH secretion or receptor levels. Administration of GH to lactating cows increased the activity of mammary 5'D twofold (Capuco et al, 1989), thus enhancing the metabolic priority of the udder (Kahl et al, 1995). Significant independent associations of serum T 4 with T 3 and IGF-I levels during the puerperium were found in two experiments involving 60 healthy cows .…”
Section: Basic Physiology Nutritional Factors Influencing Thyroid Fumentioning
confidence: 68%
“…In cattle the plasma levels of thyroid hormones may be altered also by other nutrition-and metabolism-related factors, such as selenium and/ or iodine deficiency/supplementation (Wichtel et al, 1996;Awadeh et al, 1998), growth hormone releasing factor and somatotropin administration (Kahl et al, 1995), providing fat-or starchenriched diet (Bunting et al, 1996;Romo et al, 1997;Blum et al, 2000), and feed contaminants, for instance goitrogen chemicals (Gennano-Soffietti et al, 1988;Bernal et al, 1999;rift et al, 1999a, b) and certain ergot like alkaloids produced by endophyte fungi (Neotyphodium coenophialum) of tall fescue (Festuca arundinacea; known as a really existing form on feed contamination only in North America) (Hurley et al, 1981;Browning et al, 1998Browning et al, , 2000.…”
Section: Basic Physiology Nutritional Factors Influencing Thyroid Fumentioning
confidence: 99%
“…Thus, thyroid hormone status may influence feed intake, which subsequently affects IGF‐I levels, and may modify IGF‐I concentrations through effects on GH secretion or receptor levels. On the other hand, administration of GH to lactating cows increased the activity of mammary 5′D twofold (Capuco et al, 1989), thus enhancing the metabolic priority of the udder (Kahl et al, 1995). Significant independent associations of serum T4 with T3 and IGF‐I levels during the puerperium were found in two experiments involving 60 healthy cows (Nikolić et al, 2001b).…”
Section: Discussionmentioning
confidence: 99%